PENGUATAN KAPASITAS PELAKU UMKM PANDE BESI DALAM MENERAPKAN KESELAMATAN KERJA MELALUI SOSIALISASI DAN PENDAMPINGAN (KELOMPOK UMKM PANDE BESI DESA SEGARAN, KEC. DELANGGU KAB. KLATEN) - Ahmad Hidayawan; Andri Kurniawan; Bagas Wahyu Adhi; Beni Setiyanto; Dhonna meylida; Annas Saiful Rohman; Hendramawat Aski Safarizki (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The blacksmith business in Segaran Village, Delanggu Subdistrict, Klaten Regency is one of the SMEs with high economic potential but lacks in the implementation of occupational health and safety (OHS) standards. This condition leads to high risks of workplace accidents such as burns, sharp tool injuries, and exposure to fumes and extreme heat. This community service activity aimed to enhance the awareness and capacity of SME actors in applying OHS principles through socialization and direct assistance. The methods included observation, interviews, education, PPE usage simulations, and behavior change monitoring. The results indicated an increase in OHS awareness and practices, including the use of personal protective equipment and better workspace organization. The assistance encouraged the creation of a safer and more sustainable work culture. This activity had a positive impact on the productivity and safety of blacksmith SME workers.